THE EFFECT OF MAULI BANANA STEM EXTRACT GEL (Musa acuminata) APPLICATION IN CONCENTRATION OF 37.5% ON EPITHELIAL THICKNESS (Research report) - Monica Thiodora Limay; Maharani Laillyza Apriasari; Irham Taufiqurrahman (Dentino : Jurnal Kedokteran Gigi, 2019)
Background: Injury is a state of damage or loss of tissue that can be caused by physical action. Plants that can be used in wound healing is mauli banana stem.  Mauli banana stem extract gel concentration of 37.5% contains tannins and saponins which have potential as immunomodulators. Previous research has stated that mauli banana stem extract gel concentration of 37.5% can cure traumatic ulcers. Purpose: To prove the effect of mauli banana stem (Musa acuminate) extract gel application in concentration of 37.5% on epithelial thickness in wistar rat’s (Rattus novergicus) oral mucosa lesions  on the 7th day of wound healing process. Method and material: This research was a true experimental research with posttest only control group design. It used 3 treatment groups consisted of a group which was given mauli banana stem (Musa acuminata) extract gel concentration of 37.5%, hydroxypropyl methylcellulose gel (HPMC) and patent drug containing Aloe vera extract gel. Results: The mean of  epithelial thickness in the wound healing process on the 7th day in treatment group, negative control group, and positive control grou were 119.1857 μm, 82.4563 μm, and 90,5937μm respectively . One-way Anova's test showed that there is a difference between the result of the treatment groups. Post hoc LSD test showed significant difference of epithelial thickness between mauli banana stem extract concentration of 37.5% group and hydroxypropyl methylcellulose gel (HPMC) group. There is no significant differerence between mauli banana stem extract gel concentration of 37.5% group and the patent drug containing Aloe vera extract gel group. Conclusion: The application of mauli banana stem extract gel in concentration of 37.5% can increase epithelial thickness in oral mucosa on the 7th day of wound healing process